2008
DOI: 10.1590/s0100-879x2008001200008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic head and neck physical examination as a predictor of obstructive sleep apnea in class III obese patients

Abstract: Our aim was to determine if anatomical abnormalities of the upper airway (UA) and facial skeleton of class III severely obese patients are related to the presence and severity of obstructive sleep apnea syndrome (OSAS). Forty-five patients (69% females, mean age 46.5 ± 10.8 years) with a body mass index (BMI) over 40 kg/m 2 underwent UA and facial skeletal examinations as well as polysomnography. Mean BMI was 49 ± 7 kg/m 2 and mean neck circumference was 43.4 ± 5.1 cm. Polysomnographic findings showed that 22%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 24 publications
(37 reference statements)
4
25
1
12
Order By: Relevance
“…Moreover, overjet/overbite values were normal, thereby denoting good incisor dental occlusion and good skeletal relationship between the jaws. These data are in agreement with studies that found that no abnormalities in the facial skeleton were associated with OSAHS in patients with severe obesity (14).…”
Section: Further Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, overjet/overbite values were normal, thereby denoting good incisor dental occlusion and good skeletal relationship between the jaws. These data are in agreement with studies that found that no abnormalities in the facial skeleton were associated with OSAHS in patients with severe obesity (14).…”
Section: Further Discussionsupporting
confidence: 93%
“…The dentofacial characteristics of patients with OSAHS (whether obese or non‐obese) must be evaluated before the appropriate treatment is offered. This investigation includes a guided patient history, systematic physical examination of the head and neck, nasal evaluation and some kind of imaging evaluation of the airway and dentofacial morphology, with the investigation of hard and soft tissues (3,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde OUAS'li olanlar ile olmayanların karşılaştırıldığı çalışmalarda 30,31 septal deviasyon ve konka hipertrofisine OUAS'lilerde daha sık rastlanıldı [bir çalış-mada 30 bu değerler sırasıyla OUAS'li olmayanlarda %10 ve %30; OUAS'lilerde %23 ve %65,7 olarak bildirilmiştir] ancak bu çalışmalarda OUAS'liler pozisyonel olup olmadıklarına göre gruplandırılmamıştır.…”
Section: Discussionunclassified
“…2,33,34 Bizim çalışmamızda hem pozisyonel hem pozisyonel olmayan hasta gruplarında 3.-4. derece Mallampati skoru sık bulunmuştur. Sayısal olarak POH grubumuzda daha yüksek olsa da gruplar arasında anlamlı bir fark saptanmamıştır; Martinho 30 ve arkadaşlarının çalışması ile uyumlu bir şekilde, AHİ ile bu skor arasında bir ilişki tespit edilmemiştir.…”
Section: Discussionunclassified
“…These processes were conducted using an Embla N7000 system (Medcare-Embla®, Reykjavik, Iceland) using Somnologica version 3.3.1 (Medcare-Embla®, Reykjavik, Iceland). This system and software are used in many sleep studies 25-28…”
Section: Methodsmentioning
confidence: 99%